2003
DOI: 10.1046/j.1365-2265.2003.01762.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum concentrations of remnant‐like particles in hypothyroid patients before and after thyroxine replacement

Abstract: Hypothyroidism seems to be associated with a decrease in metabolism of serum RLPs. Such altered metabolism of RLPs may be related to the decreased activities of LPL and HTGL and can be corrected by T4 replacement therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…These results may be explained in part by findings in previous studies. LPL and HTGL, which are essential for the degradation of chylomicrons or chylomicron remnants, were demonstrated to significantly increase after T 4 replacement [10,12]. Hepatocyte B-E receptors that are responsible for the uptake of LDL and chylomicrons were depressed in subjects with hypothyroidism, with an increase in expression in response to the administration of thyroid hormone [25,26].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These results may be explained in part by findings in previous studies. LPL and HTGL, which are essential for the degradation of chylomicrons or chylomicron remnants, were demonstrated to significantly increase after T 4 replacement [10,12]. Hepatocyte B-E receptors that are responsible for the uptake of LDL and chylomicrons were depressed in subjects with hypothyroidism, with an increase in expression in response to the administration of thyroid hormone [25,26].…”
Section: Discussionmentioning
confidence: 98%
“…With regard to the TG-rich lipoprotein in hypothyroidism, we previously reported the disturbed metabolism of remnant lipoprotein in overt hypothyroidism (OH) [12] and subclinical hypothyroidism (SH) [13].…”
Section: Resultsmentioning
confidence: 99%
“…However, the rat and mouse, commonly used animals for T 3 and TR studies, differ from humans in their response to T 3 . Whereas LPL activity positively correlates with TH levels in humans (9,11), hypothyroidism in rats increases both adipose and heart LPL mass and activity via a translational mechanism involving its 3Ј-untranslated region (57), whereas T 3 reverses these effects (58). Accordingly, PTU-induced hypothyroidism in rats has been associated with reductions in plasma TG (49,50,59,60).…”
Section: Discussionmentioning
confidence: 99%
“…Such elevation in TG levels has been attributed to low lipoprotein lipase (LPL) (9) or low hepatic triglyceride lipase activities (6,10,11). In contrast, hyperthyroid patients exhibit elevated rates of clearance of VLDL and normal or decreased circulating TG levels (6), whereas treatment with thyroid hormones (TH) is associated with elevation in both LPL and hepatic triglyceride lipase activities (9,10,11) and concomitantly with a tendency to TG lowering (6,9,11). At present, the molecular mechanisms by which TH may regulate lipase activities and circulating TG levels in humans remain to be defined.…”
mentioning
confidence: 99%
“…These data suggested that lower thyroid hormone was associated with the accumulation of apoB-48-containing lipoproteins (CM and CMR) because the activities of LPL and HTGL were impaired in patients with hypothyroidism. Moreover, since many studies reported that there were significant changes in LDL-C after L-T4 replacement in patients with OH 7,[38][39][40] , we investigated changes in serum apoB-48 after L-T4 ApoB-48 was measured before and after L-T4 treatment. After L-T4 replacement, serum apoB-48 decreased in 13 patients with OH (p<0.05).…”
Section: Discussionmentioning
confidence: 99%